Quantification of tannins in wet fermented cocoa beans by UV-Vis Spectrophotometric analysis at 500nm to 800nm: article - M.K, Eitrah Tasnim; Jaapar, Jefri; S, Khairul Bariah (2017)
The UV - Vis spectrophotometric analysis was conducted to quantify the tannins content in the Theobroma cacao L. Colour change of extracted cocoa samples also have relationship to the total polyphenol content in the extracted cocoa samples.